Analisis Tingkat Keuntungan Usaha Peternak Ayam Ras Petelur Berdasarkan Skala Usaha (Studi Kasus: Kecamatan Manggis, Karangasem) - NI KOMANG AYU LENNY KOMALA DEWI; I GUSTI AGUNG AYU AMBARAWATI; I GEDE BAGUS DERA SETIAWAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Analysis of The Profitability Level of Laying Chicken Farmers Based on Business Scale (Case Study: Manggis District, Karangasem) Livestock is one of the sub-sectors that plays a critical role in supplying food needs, particularly for animals. Laying hens are one of the farms that the community has created, with eggs as the major product. Manggis District, Karangasem, is one of the ideal regions for the development of laying hens. The goal of this research is to define and assess the business earnings of laying hens based on their size of operation. The information was gathered by the distribution of questionnaires to 30 laying hen breeders. Secondary information gleaned from linked literature. The study's findings include a description of the laying hen business, which is conducted on dry land with a population of chickens ranging from 1,000 to 50,000 heads, and the workers employed are from their own families as well as from outside the community. The benefits of laying hens range depending on the size of the business. Farmers with a business scale of more than 10,000 heads get the highest profit of Rp 4,179,976,688, while farmers with a business size of fewer than 5,000 heads earn the lowest profit of Rp. 1,287,538,708. As a result, farmers in each business scale earn by 12% of overall revenue and costs incurred throughout a period of chicken growing.